2017
DOI: 10.5539/ibr.v10n5p116
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of E-HRM in Service SMEs in Jordan

Abstract: This article reviews current empirical studies on electronic Human Resource Management (E-HRM) in SMEs in Jordan and discuss some findings for future undertakings. The comprehensive review is composed of related studies extracted from the online index or data base of the various journals. Contextual structure had been presented to have a clear mapping and understanding with the proceedings. It also included some studies of E-HRM outside Jordan to supplement the insufficiency and reliability of the comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Jordanian industries are required to have an innovation base and knowledge infrastructure (Hajir et al, 2015), and this is reflected in the financial performance as well as other variables such as knowledge and human resource management (Migdadi et al, 2017). There is an issue reported in the implications of the human resource management in the SMEs in Jordan as mentioned by Roman (2017). He stated that the implication of human resource in Jordan is critical and is discussed either in the context of human resource management or electronic human resource practices in Jordanian service SMEs.…”
Section: Smes Industry In Jordanmentioning
confidence: 99%
See 2 more Smart Citations
“…Jordanian industries are required to have an innovation base and knowledge infrastructure (Hajir et al, 2015), and this is reflected in the financial performance as well as other variables such as knowledge and human resource management (Migdadi et al, 2017). There is an issue reported in the implications of the human resource management in the SMEs in Jordan as mentioned by Roman (2017). He stated that the implication of human resource in Jordan is critical and is discussed either in the context of human resource management or electronic human resource practices in Jordanian service SMEs.…”
Section: Smes Industry In Jordanmentioning
confidence: 99%
“…The private economy in Jordan is comprised almost entirely of SMEs. Most Jordanian SMEs work within the formal sector and are registered as required by the law (Roman, 2017). Formal SMEs play a significant role in employment, as they employ approximately 71.4% of the private sector's workforce and almost 49.4% of all the personnel in the country's private and public sectors (Assaad & Amer, 2008;Assaad et al, 2018a;Assaad et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-HRM is an internet grounded resolution that provides an virtual real-time HRM solution using the most recent web application technologies (Roman, 2017). The concept of E-HRM was created when DeSanctis (1986) presented a description of HR info system (HRIS) that is still in use today.…”
Section: Introductionmentioning
confidence: 99%
“…New perspectives on human resource management (HRM) have suggested that electronic human resource management (e-HRM), which applies applications supported by information technology (IT) to deliver human resource (HR) services, adds value for employees, managers, HR professionals, and the organization as a whole (Bondarouk, Parry, & Furtmueller, 2017;Bondarouk & Ruël, 2013;Parry, 2011;Geetha, 2014;Roman, 2017;Ruël & van der Kaap, 2012). Conversely, the conventional perspective of HRM suggests that paper-based, face-to-face HR systems, wherein employees and managers directly interact with the staff of the HRM department, add value to the organization (Fey, Björkman, & Pavlovskaya, 2000).…”
Section: Introductionmentioning
confidence: 99%